Cardiac Stem Cell Hybrids Enhance Myocardial Repair. Issue 8 (25th September 2015) - Quijada, Pearl; Salunga, Hazel T.; Hariharan, Nirmala; Cubillo, Jonathan D.; El-Sayed, Farid G.; Moshref, Maryam; Bala, Kristin M.; Emathinger, Jacqueline M.; De La Torre, Andrea; Ormachea, Lucia; Alvarez, Roberto; Gude, Natalie A.; et al.
<x xml:space="preserve">Abstract</x> Rationale: Dual cell transplantation of cardiac progenitor cells (CPCs) and mesenchymal stem cells (MSCs) after infarction improves myocardial repair and performance in large animal models relative to delivery of either cell population. Objective: To demonstrate that CardioChimeras (CCs) formed by fusion between CPCs and MSCs have enhanced reparative potential in a mouse model of myocardial infarction relative to individual stem cells or combined cell delivery. Methods and Results: Two distinct and clonally derived CCs, CC1 and CC2, were used for this study. CCs improved left ventricular anterior wall thickness at 4 weeks post injury, but only CC1 treatment preserved anterior wall thickness at 18 weeks. Ejection fraction was enhanced at 6 weeks in CCs, and functional improvements were maintained in CCs and CPC+MSC groups at 18 weeks. Infarct size was decreased in CCs, whereas CPC+MSC and CPC parent groups remained unchanged at 12 weeks. CCs exhibited increased persistence, engraftment, and expression of early commitment markers within the border zone relative to combinatorial and individual cell population–injected groups. CCs increased capillary density and preserved cardiomyocyte size in the infarcted regions suggesting CCs role in protective paracrine secretion. Conclusions: CCs merge the application of distinct cells into a single entity for cellular therapeutic intervention in the progression of heart failure. CCs are a novel cell therapy that improves on combinatorial cell approaches to support myocardial regeneration.